PERANCANGAN CREATIVE JOURNAL SEBAGAI MATERI PENDUKUNG DREAM SETTING CANVAS - Ellen Agustine Saputra (Jurnal Dimensi DKV Seni Rupa dan Desain, 2019)
AbstractCreative Journal Design as the Dream Setting Canvas Supporting Media. Dream Setting Canvas is a dream achievement media for young people’s dream achievement, which has been applied to several empowerment programs in several non-profit organizations such as Wahana Visi Indonesia and East Bali Poverty Project. In its application, Dream Setting Canvas has weaknesses, of which the target audience has difficulty in analyzing dreams, strategies, and time without assistance. Moreover, without understanding the true essence of analyzing dreams, strategies and time, this method is not completely effective in helping young people achieve and realize their dreams. This research used qualitative research methods. Data collection used literature study, exploration, interviews with interviewees as well as distributes surveys both offline and online. The research results showed that the creative journals design could supportthe target audience to understand the topic and definition of each block in the Dream Setting Canvas.    AbstrakPerancangan Creative Journal sebagai Media Pendukung Dream Setting Canvas. Dream Setting Canvas merupakan media pencapaian mimpi anak muda yang sudah diterapkan pada beberapa program empowerment di beberapa organisasi non-Profit seperti Wahana Visi Indonesia dan East Bali Poverty Project. Pada penerapannya, Dream Setting Canvas memiliki kelemahan, di mana target audiens kesusahan dalam menganalisis mimpi, strategi, serta waktu tanpa pendampingan. Selain itu, tanpamemahami esensi sebenarnya dalam menganalisis mimpi, strategi serta waktu, metode ini tidak sepenuhnya efektif dalam membantu anak muda mencapai dan merealisasikan mimpinya. Penelitian ini menggunakan metode penelitian kualitatif. Pengumpulan data menggunakan studi literatur, eksplorasi, wawancara dengan narasumber serta membagikan survei baik secara offline maupun online. Hasil penelitian menunjukkanbahwa perancangan creative journal dapat mendukung target audiens untuk memahami topik dan definisi setiap blok pada Dream Setting Canvas